Climate Security Webinar: Benefits of Climate Adaptation for Poverty Reduction & Gender Equality - CGIAR (CGIAR, 2023)
Depending upon the source, regenerative or agroecological productions systems are new or old, experimental or time-tested, thwarted by significant barriers to scale or poised to displace conventional agriculture by 2050. What can be said of the “state of science” looking across different knowledge types from diverse stakeholders – scientists, farmers, Indigenous land stewards, companies? And what are the critical priorities to ensure that regenerative and agroecological transitions deliver benefits not just for climate and nature but for producers, landscape stewards, and communities?